Cloud Microphysical Properties of a Typical Spring Hail Event in Yunnan - Zheng, Jiao; Guo, Xin; Fu, Danhong; Li, Yingfa; Guo, Xueliang (Ying yong qi xiang xue bao = Quarterly journal of applied meteorology, 2024)
Synoptic conditions and microphysical formation mechanisms for hail events form the basis for investigating hail suppression technology. There are few relevant studies on hail formation mechanisms in spring in southern China. Most previous theories on hail formation are primarily based on numerical simulations and lack sufficient validation through observations. The atmospheric circulation, stratification, and hail microphysical properties of a typical spring hail event of Honghe in Yunnan on 28 March 2023 are investigated using meteorological and C-band dual-pol radar data. The hail formation mechanisms are compared with those derived from a cloud model with hail-bin microphysics. Results indicate that the synoptic conditions for the hail process are closely associated with the south branch of the westerly winds, which are caused by the blocking effect of the Tibetan Plateau, and the warm moist air carried by the southwesterlies around the western edge of the South Asian tropical high. Due to the relatively weak thermodynamics in spring, small-sized hail below 10 mm is predominant at the surface, with the maximum hail size reaching 20 mm. The microphysical structure of the hail cloud features a warm base and a highly active warm rain process. The dual-polarization radar products of differential reflectivity(ZDR), specific differential phase(KDP) and correlation coefficient indicate that during the initial stage of hail formation, the hail formation region consisted of spherical-shaped hail and supercooled raindrops. It suggests that hail embryos are formed through the freezing process of small-sized supercooled raindrops. As the hail embryos descend, the radar reflectivity increased and the particle shape tended to become discoid, indicating that the hail undergoes a growth process through collision with supercooled cloud water during the descent. The shape also changes from spherical to plate-like. it is because during the initial stage of hail formation, raindrops carry to the upper levels by updrafts are relatively small and had spherical shapes, causing their freezing process to form nearly spherical hail embryos. These spherical hail embryos collide with supercooled cloud water and form discoid hailstones during the falling process, which is consistent with shapes of hailstones collected at the surface. Numerical simulations show that hail embryos are primarily formed through homogeneous freezing of supercooled raindrops, and the growth of these embryos depends on accretion with supercooled cloud water, which is well consistent with products by dual-pol radar.